Women in STEM in Higher Education: A Citation Analysis of the Current Literature. Issue 3 (3rd July 2019) - Blackburn, Heidi; Heppler, Jason
ABSTRACT: Increased efforts to diversify science, technology, engineering, and math (STEM) education in the United States have increased the number of studies regarding the experiences of women in STEM programs in higher education. Using citation analysis and data visualization, this study aims to determine the major publishers and journals in this area. We reviewed 647 articles published between 2007 and 2018. Citations were concentrated on a small core set of journals and then scattered over other publications. Overall, just 3% percent of the publications accounted for 25% percent of the citations. The ramifications for STEM librarians and collection development are discussed.